Análisis, diseño y construcción de un sistema informático basado en aplicación móvil y geolocalización para el registro de baches en las vías de la ciudad de Quito. - Castro Gaibor, Cristhian Javier (2018)
This document details the development life cycle of the computer system based on mobile application which uses geolocation for the registration of potholes in the roads of Quito city. This system focuses on the automation of the actual procedure carried out by the administration of each zone inside the Quito District Metropolitan Municipality, for the prioritization and attention of these anomalies. The elaboration of this project was centered in the Zone Administration "Eloy Alfaro". It consisted of doing a full analysis of the current problems, definition of the requirements, design, construction, tests and implementation of the computer system. The solution built seeks to reduce the time spent by the individuals involved on the process on each stage. The system is made up of a mobile application that allows the registration and geolocation of potholes by capturing a photograph at the site of the event. Additionally, by using this application it is possible to validate the repair of each registered pothole, which is then verified by taking another image. Finally, as part of the project, a Web application was created with the main functionality of visualize, manage, and control the records made through the mobile application.